2020
DOI: 10.1091/mbc.e20-08-0524
|View full text |Cite
|
Sign up to set email alerts
|

More than just a ticket canceller: the mitochondrial processing peptidase tailors complex precursor proteins at internal cleavage sites

Abstract: Most mitochondrial proteins are synthesized as precursors that carry N-terminal presequences. After import into mitochondria, these targeting signals are cleaved off by the mitochondrial processing peptidase MPP. Using the mitochondrial tandem protein Arg5,6 as model substrate, we demonstrate that MPP has an additional role in preprotein maturation, beyond the removal of presequences. Arg5,6 is synthesized as a polyprotein precursor that is imported into mitochondria and subsequently separated into two distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The neo-acetylated-Nt-peptides identified were mainly from the mitochondria and relate to the removal of the mitochondria targeting sequence (mitochondria transit peptide). This type of proteolytic processing is done after the protein is imported into the mitochondria and reaches the mitochondrial matrix (Friedl et al, 2020). Next, we looked for additional hints for post-translational neo-Nt-acetylation that occur following other proteolytic cleavages.…”
Section: Resultsmentioning
confidence: 99%
“…The neo-acetylated-Nt-peptides identified were mainly from the mitochondria and relate to the removal of the mitochondria targeting sequence (mitochondria transit peptide). This type of proteolytic processing is done after the protein is imported into the mitochondria and reaches the mitochondrial matrix (Friedl et al, 2020). Next, we looked for additional hints for post-translational neo-Nt-acetylation that occur following other proteolytic cleavages.…”
Section: Resultsmentioning
confidence: 99%
“…Using the precursor of mitochondrial tandem protein Arg5,6 as a model substrate from S. cerevisiae mitochondria, Friedl et al (2020) have demonstrated that MPP not only removes the N-terminal targeting sequence from this precursor tandem protein but is also required for specific internal processing generating two functional enzymes, Arg5 and Arg6. Further, in silico searching for internal matrix targeting signal-like sequences (iMTS-L) and canonical MPP cleavage sites in mitochondrial precursor proteins with composite structure in different species (Atp25 from S. cerevisiae and Emericella nidulans, Etp1, Rsm22-Cox11, and the uncharacterized SPAC22A12.08c from Schizosaccharomyces pombe, as well as RPS14 from Oryza sativa japonica) led to the identification of both types of motifs in these organisms (Friedl et al, 2020). This study indicates that internal precursor processing by MPP is conserved among fungi and plants, and possibly other eukaryotes.…”
Section: Mitochondrial Processing Peptidase Mppmentioning
confidence: 99%
“…Besides, MPP has been shown responsible for the processing of precursor proteins that are post-translationally cleaved into polypeptides functioning as separate enzymes. For example, Arg5,6 from S. cerevisiae synthesized in the cytosol is after the import into mitochondria first cleaved by MPP to be disposed of its MTS and then internally processed to form two distinct enzymes, Arg5 (N-acetyl-gamma-glutamyl-phosphate reductase) and Arg6 (acetylglutamate kinase) [29].…”
Section: Mitochondrial Processing Peptidasementioning
confidence: 99%